2022
DOI: 10.1101/2022.01.06.475118
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The biosynthetic-secretory pathway, supplemented by recycling routes, specifies epithelial membrane polarity

Abstract: In prevailing epithelial polarity models, membrane-based polarity cues (e.g., the partitioning-defective PARs) position apicobasal cellular membrane domains. Intracellular vesicular trafficking expands these domains by sorting apicobasal cargo towards them. How the polarity cues are polarized and how sorting confers long-range vesicle directionality is still unclear. Here, a systems-based approach using two-tiered C. elegans genomics-genetics screens identifies trafficking molecules that are not implicated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
43
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(54 citation statements)
references
References 66 publications
(130 reference statements)
11
43
0
Order By: Relevance
“…We conclude that bcAMs and actin are required to specify the position of apical PARs on not yet polarized membranes of still dividing and migrating intestinal cells and on already polarized but still expanding membranes of postmitotic cells within the fixed epithelium. These findings further support the proposed noncanonical function of bcAMs and actin in membrane polarity via directional trafficking that likewise operates upstream of PARs in intestinal polarity 7 . Our findings also reveal that branched chain actin dynamics functions upstream of the to date earliest polarity cue in the establishment of epithelial polarity in the C. elegans intestine.…”
Section: Unc-60 Arx-2 Cap-1 and Actin Specify The Polarized Distribut...supporting
confidence: 76%
See 4 more Smart Citations
“…We conclude that bcAMs and actin are required to specify the position of apical PARs on not yet polarized membranes of still dividing and migrating intestinal cells and on already polarized but still expanding membranes of postmitotic cells within the fixed epithelium. These findings further support the proposed noncanonical function of bcAMs and actin in membrane polarity via directional trafficking that likewise operates upstream of PARs in intestinal polarity 7 . Our findings also reveal that branched chain actin dynamics functions upstream of the to date earliest polarity cue in the establishment of epithelial polarity in the C. elegans intestine.…”
Section: Unc-60 Arx-2 Cap-1 and Actin Specify The Polarized Distribut...supporting
confidence: 76%
“…To start mapping vesicle trajectories through C. elegans intestinal development, we directed expression of the ubiquitous RAB-11 (marking endosomes with presumed apical directionality) and RAB-10 (marking endosomes with presumed basolateral directionality to the intestine by elt-2 to visually resolve their subcellular positions in both pre- and post-intercalation intestinal cells ( 27 ; Methods). We found that RAB-11+ post-Golgi vesicles, previously identified as apical polarity cues 7 , indeed exhibit a bcAM/actin synchronous positional shift from the cytoplasm to the apical domain in the developing wild-type intestine, consistent with a directional change of presumed apical vesicle trajectories during membrane polarity establishment (Fig.6b). Based on this finding we next examined whether the positioning of these and other, not yet well mapped, vesicle populations was dependent on bcAMs/actin during de novo polarized membrane biogenesis.…”
Section: Main Textsupporting
confidence: 75%
See 3 more Smart Citations